Hydrostatic investigations on subglacial meltwater: implications for the formation of streamlined bedforms and subglacial lakes, East Antarctica - Sawagaki ,Takanobu; Hirakawa ,Kazuomi (National Institute of Polar Research, 2002)
P(論文) Streamlined bedforms and small erosional marks observed on the Soya Coast, East Antarctica, are interpreted to have been formed by subglacial meltwater The source of water is attributed to subglacial lakes that may have existed beneath the upper part of the Mizuho Plateau In order to evaluate the subglacial meltwater hypothesis, two theoretical investigations were carried out, one to model the formation of subglacial lakes in the Shirase drainage basin, and the second to estimate the conformity of water flow beneath the ice sheet to underlying topography In the first investigation we found that several subglacial lakes would have formed in the bed depressions with the water surfaces determined by englacial equipotential surfaces In the second investigation, several ice thicknesses and their surface gradients were determined in which agreement between potential gradients and the observed bedform distribution was found These experimental results add to the existing observations and inductive reasoning supporting a subglacial hydraulic origin for bedforms along the Soya Coast According to the results, possible causes of sudden subglacial outburst floods and their influence are discussed If subglacial water storage and sudden discharge occurred, a combination of water accumulation beneath the ice sheet and discharge of this water could make the ice sheet unstable leading to the rapid melting of the ice sheet supplying huge amount of meltwater to the ocean and formation of local ice streams Such subglacial meltwater events in Antarctica possibly contributed some global meltwater pulse events during MIS-3 or post-LGM periods departmental bulletin paper